2018
DOI: 10.1039/c8sc02000k
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a diagnostic structural motif reveals a new reaction intermediate and condensation pathway in kraft lignin formation

Abstract: Detailed structural analysis of industrial and model kraft lignins reveals an important new reaction intermediate and condensation pathway operating during kraft pulping.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
211
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 178 publications
(219 citation statements)
references
References 88 publications
8
211
0
Order By: Relevance
“…Stilbenoid units (SB1 and SB5) were additionally included in this analysis, as we have recently identified them as particularly abundant units in softwood kraft lignin. [12,46] The improved correlation resultss uggested that the models shouldb ea ble to predict the properties of new,l ignin samples obtained independently from the original calibration set with reasonably high accuracy. This is demonstrated by the analysiso favalidation set of lignins.…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…Stilbenoid units (SB1 and SB5) were additionally included in this analysis, as we have recently identified them as particularly abundant units in softwood kraft lignin. [12,46] The improved correlation resultss uggested that the models shouldb ea ble to predict the properties of new,l ignin samples obtained independently from the original calibration set with reasonably high accuracy. This is demonstrated by the analysiso favalidation set of lignins.…”
Section: Resultsmentioning
confidence: 96%
“…Using the previously determined optimal method for processing the IR spectra, this focused set of lignins produced significantly improved results with higher R 2 Cal., R 2 CV and lower REs for the PLS models (Table ). Stilbenoid units (SB1 and SB5) were additionally included in this analysis, as we have recently identified them as particularly abundant units in softwood kraft lignin . The improved correlation results suggested that the models should be able to predict the properties of new, lignin samples obtained independently from the original calibration set with reasonably high accuracy.…”
Section: Resultsmentioning
confidence: 99%
“…In recent years, apart from its combustion for energy, isolation of lignin originating from industrial kraft pulping processes as well as biorefinery plants producing ethanol as biofuel has seen a steady increase. Parallel to the surge in the availability of lignin, nano‐ and microscaled lignin‐based materials and state‐of‐the‐art analytical techniques that provide a more detailed understanding of the structural differences of the various lignins were developed …”
Section: Introductionmentioning
confidence: 99%
“…[1,2] However, the valorization of lignin remains a challenge due to its complex structure. [3][4][5][6][7][8][9] Its inherent heterogeneity is a result of at least three contributing factors: i) Lignin is made up of variable amounts of 3 possible C9 monomers (H, G, and S, Figure 1A); ii) different types of linkages are formed by coupling of the C9 monomers, the most abundant of which is the β-O-4 linkage ( Figure 1B); iii) Lignin has considerably higher variation in chain lengths compared to standard polymers leading to a high polydispersity (2.0-9.0 depending on the source and pretreatment method used, Figure 1C). [10] It is becoming evident that for any lignin application, discrete regions of the bulk molecular weight distribution (MWD) will be most suitable.…”
Section: Introductionmentioning
confidence: 99%